The Effect of Online Low-intensity Exercise Training on Fitness and Cardiovascular Parameters - Kikuchi, Naoki; Mochizuki, Yukina; Kozuma, Ayumu; Inoguchi, Takamichi; Saito, Mika; Deguchi, Minoru; Homma, Hiroki; Ogawa, Madoka; Hashimoto, Yuto; Nakazato, Koichi; Okamoto, Takanobu (International Journal of Sports Medicine, 2021)
Online exercise is undoubtedly useful and important; however, chronic adaptations to online exercise, particularly strength gain, muscle hypertrophy, and cardiovascular parameters, remain unclear. We investigated the effect of online exercise training using Zoom on fitness parameters compared with the same exercises supervised directly. In the present study, 34 subjects (age: 42.9±14.4 years) were included. Twenty-three subjects performed 8 weeks of body mass-based exercise training online using Zoom, and eleven subjects performed the same exercise supervised directly as the control group. The subjects performed low-load resistance exercises twice a week for 8 weeks for a total of 16 sessions. The sessions included 9 exercises: leg raises, squats, rear raises, shoulder presses, rowing, dips, lunges, Romanian dead lifts, and push-ups. Chair-stand, push-up, and sit-and-reach tests were performed on all subjects. Overall, the home exercise program effectively increased strength and muscle mass and decreased blood pressure and arterial stiffness, but there were no differences between the groups. Changes in chair-stand and sit-and-reach test results were higher in the control group than in the online group. Our results show that there is a similar training response to body mass-based training in both groups, even with virtual experiences using Zoom.
Keywords: home-based exercise; online training; fitness; muscle hypertrophy; arterial stiffness